2012
DOI: 10.1007/s10495-012-0788-0
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo molecular imaging probe 18F-Annexin B1 for apoptosis detection by PET/CT: preparation and preliminary evaluation

Abstract: There is an increasing need to develop non-invasive molecular imaging strategies for visualizing and quantifying apoptosis status of diseases (especially for cancer) for diagnosis and monitoring treatment response. Since externalization of phosphatidylserine (PS) is one of the early molecular events during apoptosis, Annexin B1 (AnxB1), a member of Annexins family with high affinity toward the head group of PS, could be a potential positron emission tomography (PET) imaging probe for imaging cell death process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Oborski et al subsequently reported the successful use of 18 F-ML-10 PET for the early response assessment of radiotherapy in glioblastoma multiforme patients 32 . In addition to 18 F-ML-10, the radionuclides 99m Tc- and 18 F-labeled Annexins play important roles in apoptosis imaging 33 , 34 . However, these Annexin-based probes have been associated with substantial challenges in monitoring the therapy efficacy, such as AAT, in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Oborski et al subsequently reported the successful use of 18 F-ML-10 PET for the early response assessment of radiotherapy in glioblastoma multiforme patients 32 . In addition to 18 F-ML-10, the radionuclides 99m Tc- and 18 F-labeled Annexins play important roles in apoptosis imaging 33 , 34 . However, these Annexin-based probes have been associated with substantial challenges in monitoring the therapy efficacy, such as AAT, in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Cells at the logarithmic growth phase were harvested and adjusted to a concentration of 10 6 /mL in PBS, pH 7.5. Binding assays were performed as previously described [ 19 , 21 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…N-succinimidyl 4-fluorobenzoate (SFB) and ethyl 4-(trimethyl-ammonium) benzoate ( 18 F-SFB precursor) were prepared as previously described (13,14), with some modifications. 18 F-CRTpep was synthesized using modifications of previously reported methods (15,16). First, 18 F-SFB was synthesized to an approximately 30%240% (non-decay-corrected) radiochemical yield; the radiochemical purity was more than 98%.…”
Section: Radiochemistry For 18 F-crtpep Synthesismentioning
confidence: 99%